The hidden window mystery - Keene, Carolyn (New York, NY : Grosset & Dunlap, Incorporated : Imprint of Putnam Publishing Group, 1956)
Nancy Drew visits her cousin in Virginia hoping to locate a missing stained-glass window.
760
Accelerated Reader AR
Keywords: Mystery and detective stories